Evaluating glucose‐lowering treatment in older people with diabetes: Lessons from the IMPERIUM trial. Issue 8 (11th March 2020) - Sinclair, Alan J.; Heller, Simon R.; Pratley, Richard E.; Duan, Ran; Heine, Robert J.; Festa, Andreas; Kiljański, Jacek
Abstract: Understanding the benefits and risks of treatments to be used by older individuals (≥65 years old) is critical for informed therapeutic decisions. Glucose‐lowering therapy for older patients with diabetes should be tailored to suit their clinical condition, comorbidities and impaired functional status, including varying degrees of frailty. However, despite the rapidly growing population of older adults with diabetes, there are few dedicated clinical trials evaluating glucose‐lowering treatment in older people. Conducting clinical trials in the older population poses multiple significant challenges. Despite the general agreement that individualizing treatment goals and avoiding hypoglycaemia is paramount for the therapy of older people with diabetes, there are conflicting perspectives on specific glycaemic targets that should be adopted and on use of specific drugs and treatment strategies. Assessment of functional status, frailty and comorbidities is not routinely performed in diabetes trials, contributing to insufficient characterization of older study participants. Moreover, significant operational barriers and problems make successful enrolment and completion of such studies difficult. In this review paper, we summarize the current guidelines and literature on conducting such trials, as well as the learnings from our own clinical trial (IMPERIUM) that assessed different glucose‐lowering strategies in older people with type 2 diabetes. We discuss the importance of strategies to improve study design, enrolment and attrition. Apart from summarizing some practical advice to facilitate the successful conduct of studies, we highlight key gaps and needs that warrant further research.